Custo Direto Médico-Hospitalar da recaída em esquizofrenia em três serviços na cidade de São Paulo no ano de 2006 - Daltio, Claudiane Salles [UNIFESP] (2009)
Aims: Significant cost is associated with schizophrenia and relapses are one significant cost element. Objective: Assess the direct medical costs associated with schizophrenia relapses at three mental health services in the city of São Paulo: a public state hospital (HP); a hospital affiliated with the Brazilian Unified Healthcare System -SUS (HCC); a Community Psychosocial Service Center (CAPS). Methods: We reviewed the charts of 90 patients with schizophrenia who had been i n services in 2006. We evaluated the r esources used dur ing the time these patients were in services. Results: The Mean Direct Medical Cost of schizophrenia relapses was, per patient, Rdollar 8.167,58 i n HP; Rdollar 4.605,46 at the CAPS and Rdollar 2.397,74 in HCC ( Rdollar 2 / 1 USdollar). The most significant component in all cases was the daily rate. The cost of medication differed depending on whether typical or atypical antipsychotics were used. CAPS making more use of atypical drugs. Conclusion: The costs associated with schizophrenia relapses justify investments in antipsychotic drugs and strategies to reduce the need for mental health services, especially hospitals. The cost associated with treating patients in a CAPS is intermediate and has the added benefit of not depriving patients from their family life.